Effect of prolonged electrode potential cycling on the conduction properties of poly(o-aminophenol) film electrodes - Tucceri, Ismael Ricardo (2014)
The aim of this work was to study the effect of prolonged potentiodynamic cycling (PPC) on the conducting properties of poly(oaminophenol (POAP) film electrodes. PPC reduces strongly the electron transport rate at POAP films. This effect is called herein deactivation. Cyclic Voltammetry (CV), Rotating Disc Electrode Voltammetry (RDEV) and Electrochemical Impedance Spectroscopy (EIS) were employed in this study. The attenuation of the voltammetric response of the polymer with the increase in the number of oxidation-reduction cycles allowed one to define a degree of deactivation. RDEV and EIS were employed to obtain the dependence of some charge-transport parameters on the degree of deactivation of the polymer. RDEV data were interpreted in terms of the electron hopping model. Impedance spectra were analysed on the basis of a model which considers a protonation reaction coupled with a self-exchange process between oxidized and reduced sites. POAP films maintain their conducting properties almost unaltered for about 500 potential cycles at a scan rate of 0.010 Vs-1. However, a loss of conductivity was observed as the number of potential cycles was extended beyond 500.